(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
Sedimentological analyses of sandstones and conglomeratic facies within the Lokoja Formation belonging to the southern part of the Bida Basin around Lokoja and environs were carried out with the aim of deducing their depositional environment. Based on field observations and analysis of 33 representative samples, there is no occurrence of shale within the Lokoja Formation as earlier reported in the area. Results of glanulometric anal ysis and parameters as well as bivariate plots show that the conglomerates are dominantly paraconglomerates and are essentially polymictic in nature. Thus, this is an indication that a fluvial sedimentation was responsible for the accumulation of sandstones of the Lokoja Formation. In support of this, evidence depicting characteristic bladed fabric was observed in 150 samples subjected to pebble morphometric analysis. This to a large extent also suggest a fluvial (river) depositional environment for the conglomeratic facies. Scatter plots of roundness versus elongation ratio delineate angular to sub-rounded pebbles and such grain shape delineation and the low roundness values for the pebbles (average, 0.55) are an indication of a fluvial environment of deposition and short transportation history. However, some pebbles indicate marine influence as some of the morphometric data plot within the littoral environment.